Family, patronage, and power networks in the cathedral cabildo of the bishop of popayán, 1600-1728 - Abadía Quintero, Carolina (2021)
The ecclesiastical councils played a decisive role in the ecclesiastical administration of the Indian bishoprics since it was the corporation in which members of local family groups positioned themselves as a strategy to acquire power and prestige, or a grant from the king, appealing to the resources of ecclesiastical promotion. dictated by the Regio Patronato. Is it possible to identify this model of practices in the cathedral chapter of Popayán? How does the promotion of an ecclesiastic influence his family lineage or the support of a protector? The objective of this text is to show how in the seventeenth century, various cases of networks and lineages that achieved a prebend in the Pagan cathedral chapter stand out, for these documents from the General Archive of the Indies and the Central Archive of Cauca have been consulted, which They allow us to understand that the Payanese cathedral chapter was not exempt from this type of binding political logic.